Factor analysis of body measurements of bulls of local cattle of Tripura, India - MAJUMDAR, SURITA; BORA, PRINCELINA; BORA, ARINDOM; CHAUDHARY, J K; SINGH, N SHYAMSANA; MAYENGBAM, PRAVA; TOLENKHOMBA, T C (The Indian Journal of Animal Sciences, 2021)
Eighteen different biometric traits (body length, height at wither, heart girth, paunch girth, arm length, elbow length, fore-shank length, thigh length, hind shank length, pes length, tail length, switch length, ear length, head length, eye to eye space, circumference of horn, space between horn and horn length) in 50 bulls of Tripura local cattle were recorded from 3 districts (viz. North Tripura, South Tripura and West Tripura) of Tripura, India and analyzed by Principal component analysis to explain body conformation. The average of these various traits indicates that local cattle Tripura is of smaller type of cattle breed. Factor analysis with promax rotation revealed six factors which explained about 76.64% of the total variation. Factor 1 described the general body conformation and explained 21.85% of total variation. It was represented by significant positive high loading of body length, height at wither, head length, circumference of horn, distance between horns and horn length. The communality ranged from 0.535 (head length) to 0.890 (fore-shank length) and unique factors ranged from 0.465 to 0.110 for all the 18 different biometric traits. The result suggests that principal component analysis (PCA) could be used in breeding programs with a drastic reduction in the number of biometric traits to be recorded to explain body conformation.